Oral health status of children seen at a paediatric neurology clinic in a tertiary hospital in Nigeria (2012)
The study was carried out to determine oral health status and oral health needs of children presenting at the paediatric neurology clinic of the University College Hospital, Ibadan, Nigeria. Diagnosis of each child’s disability was performed by the Consultant Paediatric Neurologist. Data on socio-demographic characteristics and previous history of trauma to the o rofacial structures for each child were obtained and intraoral examinations were done using WHO guide lines. Sixty-one children were diagnosed within the period of study and highest proportion (44.3%) had epilepsy while 41.0% had cerebral palsy. Prevalence of dental caries and trauma were 11.5% and 39.3% respectively while 72.1% had good oral hygiene. Despite the relatively good oral health of the children under study, periodic dental recall appointments will be beneficial in order to supervise and evaluate oral health when early detection and prevention of lesions can be instituted.